2007
DOI: 10.7202/032964ar
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Induced Seismicity in the Lake Erie-Lake Ontario Region: Reactivation of Ancient Faults with Little Neotectonic Displacement

Abstract: The two most prominent seismic zones in the Lake Erie-Lake Ontario region are associated with the Akron magnetic lineament and with the Clarendon-Linden fault. Both these features are recognized from geophysical data as regional basement structures related to the Grenville collisional orogen. Neotectonic displacement is not geologically evident, although Paleozoic reactivation is manifested by the Clarendon-Linden fault. We have sharpened the definition of seismic zones in the region by introducing newly disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…There were four earthquakes in Lake County and one earthquake in Ashtabula County during our 2010–2014 study time frame, which was interesting since these counties hosted seismic sequences that are thought to have been induced by deep wastewater disposal as far back as 1986 [ Nicholson et al , ; Seeber and Armbruster , ; Seeber et al , ; Gerrish and Nieto , ] (Figure ). We found that all five recent earthquake templates produced matching events, but the number of matches was small (2–4), and they appear to resemble more traditional foreshock/main shock/aftershock patterns.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…There were four earthquakes in Lake County and one earthquake in Ashtabula County during our 2010–2014 study time frame, which was interesting since these counties hosted seismic sequences that are thought to have been induced by deep wastewater disposal as far back as 1986 [ Nicholson et al , ; Seeber and Armbruster , ; Seeber et al , ; Gerrish and Nieto , ] (Figure ). We found that all five recent earthquake templates produced matching events, but the number of matches was small (2–4), and they appear to resemble more traditional foreshock/main shock/aftershock patterns.…”
Section: Resultssupporting
confidence: 60%
“…There were four earthquakes in Lake County and one earthquake in Ashtabula County during our 2010-2014 study time frame, which was interesting since these counties hosted seismic sequences that are thought to have been induced by deep wastewater disposal as far back as 1986 [Nicholson et al, 1988;Seeber and Armbruster, 1993; Figure 6. Magnitudes of earthquakes found through template matching in the Washington County region.…”
Section: Lake and Ashtabula Countiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The January 26, 1986, m b =4.9 Leroy earthquake and aftershocks have been correlated with the AMB (Seeber and Armbruster, 1993). Epicentral alignments along the CMBBZ/NPLZ are also conspicuous on the Niagara Peninsula (Figs.…”
Section: Seismotectonic Relations and Suggested Source Zonesmentioning
confidence: 93%
“…Dineva et al (2004) estimated that the overall magnitude threshold for the earthquake catalog in this area during 1990-2000 is about M n 2.0 based upon cumulative earthquake frequency versus magnitude relations during the period. Seismicity in the Erie-Ontario Lowlands region is clustered in two zones: western Lake Ontario-Niagara-Attica, New York seismic zone (LONASZ; Seeber and Armbruster, 1993) and Northeastern Ohio-Pennsylvania seismic zone (NEOPSZ; Dineva et al, 2004). Th e 4 August 2004 earthquake is the largest earthquake that occurred under Lake Ontario in LONASZ.…”
Section: Introductionmentioning
confidence: 99%